THE LEVEL OF COMORBIDITY AND PHYSICAL DEVELOPMENT OF PRESCHOOL CHILDREN BORN PREMATURELY (Herald of the National Children's Medical Center, 2025)
Premature babies are a risk group for many diseases associated with impaired physical and neuropsychiatric development, nutritional deficiencies and weakened immunity. They are more susceptible to infectious diseases, anemia, vitamin deficiency and digestive disorders. Studying the specifics of their health and nutritional status allows us to identify key problems and develop effective corrective measures.
Keywords: premature babies; preschool age; physical development; comorbidity; nutritional deficiencies